Preparation of planar CH3NH3PbI3 thin films with controlled size using 1-ethyl-2-pyrrolidone as solvent - Hao, Qiuyan; Chu, Yixia; Zheng, Xuerong; Liu, Zhenya; Liang, Liming; Qi, Jiakun; Zhang, Xin; Liu, Gang; Liu, Hui; Chen, Hongjian; Liu, Caichi (Journal of alloys and compounds, 2016)
Recently, planar perovskite solar cells based on CH3NH3PbI3 have attracted many researcher's interest due to their unique advantages such as simple cell architecture, easy fabrication and potential multijunction construction comparing to the initial mesoporous structure. However, the preparation of planar perovskite films with high quality is still in challenge. In this paper, we developed a vapor-assisted solution process using a novel and green solvent of 1-Ethyl-2-pyrrolidone (NEP) instead of the traditional N, N-dimethylformamide (DMF) to construct a high-quality perovskite CH3NH3PbI3 thin film with pure phase, high compactness, small surface roughness and controlled size. The phase evolution and growth mechanism of the perovskite films are also discussed. Utilizing the NEP of low volatility and moderate boiling point as solvent, we dried the PbI2-NEP precursor films at different temperature under vacuum and then obtained PbI2 thin films with different crystalline degree from amorphous to highly crystalline. The perovskite films with crystal size ranged from hundreds of nanometers to several micrometers can be prepared by reacting the PbI2 films of different crystalline degree with CH3NH3I vapor. Moreover, planar-structured solar cells combining the perovskite film with TiO2 and spiro-OMeTAD as the electron and holes transporting layer achieves a power conversion efficiency of 10.2%. [Display omitted] •A novel and green solvent of 1-Ethyl-2-pyrrolidone (NEP) was used to construct high-quality perovskite CH3NH3PbI3 thin film.•The CH3NH3PbI3 grain with different sizes ranged from hundreds of nanometers to several micrometers can be obtained.•Planar-structured perovskite CH3NH3PbI3 solar cells using NEP as solvent achieves a power conversion efficiency of 10.2%.